Assessment of Exogenous Pigmentation on Clear Elastomeric Modules: An in vitro Study - Ansari, Shaista N; Rathod, Dhananjay; Rathod, G P; Bisht, Gazal (Orthodontic Journal of Nepal, 2018)
Objective: To assess in vitro changes in the shade of clear elastomeric modules from different manufacturers influenced by exogeneous pigmentation contained in everyday dietary substances. Materials & Method: The specimen comprised of clear elastomeric modules (Group A: Libral, Group B: TP Orthodontics) which were immersed in dietary substances: ketchup, coffee, tea, pepsi & methylene blue. Their hue, saturation and intensity were figured after 72 hours by methods of Adobe photoshop CS3 to mirror the module recoloring seriousness. Result: Significant difference was found between two types of modules analyzed in this study. Ketchup and methylene blue demonstrated higher staining potential compared to other staining media. Besides, there was no significant difference in staining contrast between tea and Pepsi. Conclusion: Ketchup and methylene blue are strong staining media, ought to be avoided by the patients opting for aesthetic orthodontic appliances. Elastomeric modules manufactured by different companies have differing staining potential.